The Effectiveness of Moringa Leaf Powder Capsules (Moringa oleifera Lam.) in Reducing the Severity of Anaemia in Pregnant Women - Filda Fairuza; Sandy Rahman; Sukmiyant Sukmiyant (Poltekkes Kemenkes Surabaya, 2026)
Anaemia is an iron deficiency that causes anaemia in pregnant women, which can have a negative impact on foetal or infant growth and development during and after pregnancy. One way to increase haemoglobin levels in pregnant women with anaemia is to consume moringa leaf powder capsules (Moringa oleifera Lam.), which have haematopoietic activity and are beneficial in increasing platelet counts. The purpose of this study was to determine the effect of moringa leaf powder capsules (Moringa oleifera Lam.) on haemoglobin levels in pregnant women with mild to moderate anaemia with haemoglobin levels of 8–11 g/dL at the Reva Medika Clinic, Lebak Regency in 2025. The intervention was carried out for seven consecutive days with a dose of 2 moringa leaf capsules per day. Hemoglobin levels were measured using a digital hemoglobinometer EasyTouch® HB (Taiwan) in accordance with WHO standard procedures to ensure the accuracy of the test results. The sampling technique used was the Ishak and Michel method. The research respondents were pregnant women aged 20–35 years with a gestational age of 20–32 weeks who had mild to moderate anaemia with haemoglobin levels of 8–11 g/dL and no comorbidities. The study was conducted from January to March 2025. The results of the study after administering moringa leaf powder capsules for anaemia in pregnancy showed that the majority of pregnant women experienced mild anaemia (27 people or 84.4%) and severe anaemia (5 people or 15.6%). A significant difference was found between before and after the administration of moringa leaf powder capsules for anaemia in pregnancy. The Wilcoxon Sign Rank test showed a p-value of 0.000 0.05. It can be concluded that the administration of moringa leaf powder capsules had an effect on anaemia in pregnancy at the Reva Medika Clinic, Lebak District, in 2025.